Investigating the Efficiency of Recombinant FliC-Loaded Bacil-lus subtilis Spores in Mice Immunization against Salmonella en-terica Serovar Typhi - Nafiseh Ghorbani; Mehdi Assmar; Nour Amirmozafari; Khosrow Issazadeh (Tehran University of Medical Sciences, 2021)
Background: Bacterial spores are among the most efficient vaccine delivery vehicles. Because of their safety and efficacy, Bacillus subtilis spores are increasingly used in this regard. The negatively charged surfaces of the spores allow antigens to be adsorbed onto these structures. In this study, a candidate vaccine against Salmonella enterica serovar Typhi was adsorbed onto B. subtilis spores and the immunogenicity of the formulation was investigated in BALB/c mice. Methods: This work was performed during 2018-2019 in Islamic Azad University of Lahijan. FliC protein was recombinantly expressed in E. coli BL21 (DE3) cells and purified by affinity chromatography. On the other hand, B. subtilis strain PY79 (ATCC1609) was cultured in DSM medium and after the sporulation, FliC protein was adsorbed onto the spores in three different pH values (4, 7 and 10) and the adsorption was verified using dot-blot assay. FliC-adsorbed spores were then administered to BALB/c mice through the subcutaneous route. Mice immunization was evaluated by serum IgG assessment and challenge study. Results: FliC protein was successfully expressed and purified. Sporulation was controlled by phase-contrast microscopy. Serum IgG assay showed significant stimulation of the mice's humoral immune system. Immunized mice were able to resist bacterial infection. Conclusion: The results showed the efficiency of spores as natural adjuvants for the stimulation of mice immune system. The formulation can be exploited for the delivery of recombinant vaccines against bacterial pathogens.